The Contribution of Exposure Frequency to English to Speaking and Writing Performance of EFL Learners at Junior High School in Indonesia - Arfah, Hajriana; Zam, Ahmad Zam (Universitas Hamzanwadi, 2017)
This study was aimed at describing the contribution of exposure frequency to English (EFE) to speaking and writing English as a foreign language (EFL) learners in bilingual class setting of a state junior high school in East Lombok, which has been implementing bilingual principles (English-Indonesia) of Mathematics and Natural Science. This research is ex-post facto with correlation design. The samples were systematically selected by choosing even number of the student lists, which involved forty-six of ninety-three students of eight grade in academic year 2011/2012. Data were analyzed with regression. The calculation was done at 5% significant level.This research discovered that (1) there is a significant correlation between exposure frequency to English language and speaking performance of the students in bilingual classes by R value of .555 with probability of .00; (2) there is significant correlation between exposure frequency to English and writing performance by R value of .78 with probability of .00; (3) the EFE significantly contribute to writing performance with R Square value of .609 (60.9%); and (4) it also contribute.309 (30.9%) the students’ speaking performance.